A conceptual model of internal audit capability model (IACM) development to improve accountability of education funding management in private high schools in Semarang city - Raharjo, Tri Joko; Yulianto, Arief; Arief, Sandy; Pendriana, Yuli (Edelweiss Applied Science and Technology, 2024)
Stakeholder involvement, such as foundations in school financial management, reflects good coordination. However, the dominant authority of foundations often limits school management, particularly in financial management. This research aims to enhance internal control by adopting the Internal Audit Capability Model (IACM). While foundations can conduct audits, schools need to establish independent audit teams at the managerial level to improve accountability. This study used the Design-Based Research (DBR) method to develop a conceptual model, employing both quantitative and qualitative approaches. A total of 39 private schools in Semarang City participated, with 37 headmasters and 35 treasurers providing quantitative data. Expert interviews followed to validate the model. The research presents a framework for systemic change in financial auditing, positioning an independent school audit team as essential for financial control. This team, consisting of school practitioners, supports transparency and reduces foundation regulation rigidity. The model offers opportunities for policymakers and educational foundations to adapt the concept within the private school context, promoting decisions to reform the financial audit system, with the headmaster playing a formal audit role.